Santa Clause and children - Sahl, Ted (photographer):::Creator::::::::::::
Dressed as Santa Clause, Dennis Andrews, holds a present in his left hand and he appears to be in conversation with two small children. The child on the right is pointing to a younger child on the left, and another child can be seen smiling behind Santa. On the floor are various toys, including a toy car and a xylophone.